Work Avoidance as a Manifestation of Hostility, Helplessness, and Boredom - Jarvis, Sharon; Seifert, Tim (Alberta Journal of Educational Research, 2002)
Work avoidance is a term that describes the behavior of students who seem to make little effort to understand or complete academic tasks. Although the condition has been described in earlier studies, the causes of work avoidance have not been explored. In this study, grades 5 and 6 students who were identified as work avoidant were interviewed to determine the causes of their work avoidance. It was hypothesized that boredom, hostility, and helplessness were three possible reasons for students not exerting effort. Students' protocols indicated that they do withdraw effort for several reasons: because they are bored, as an expression of hostility toward the teacher, or because of feelings of helplessness.